1980
DOI: 10.1146/annurev.ns.30.120180.002355
|View full text |Cite
|
Sign up to set email alerts
|

Particle Collisions Above 10 TeV as Seen by Cosmic Rays

Abstract: COSMIC RAYS AND PARTICLE PHYSICS 477 chambers, with an acceptance of 0. 1 m2 sr, to giant air shower arrays with areas measured in square kilometers. Intermediate in size and energy range are large calorimeters and emulsion chambers. Collisions at 10-20 Te VThe emulsion chamber technique yields the most detailed information about properties of hadronic interactions in this energy range because it allows detection and energy estimates of single charged hadrons as well as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…This observation reveals the fact that the accelerator data on Feynman x F distributions in the fragmentation region are relevant for the analysis of secondary cosmic rays on Earth's atmosphere. A recent study supports the earlier observation of Gaisser and Yodh [31], who have shown that the superposition model is approximately applicable to the investigation of A-A collisions in high-energy cosmic-ray propagation. It may be pointed out that the muon fluxes decrease by 20% when corrected for pp collisions due to A-A collisions.…”
Section: Estimated Muon Flux Is Mainly Dependent On Z Asupporting
confidence: 86%
See 1 more Smart Citation
“…This observation reveals the fact that the accelerator data on Feynman x F distributions in the fragmentation region are relevant for the analysis of secondary cosmic rays on Earth's atmosphere. A recent study supports the earlier observation of Gaisser and Yodh [31], who have shown that the superposition model is approximately applicable to the investigation of A-A collisions in high-energy cosmic-ray propagation. It may be pointed out that the muon fluxes decrease by 20% when corrected for pp collisions due to A-A collisions.…”
Section: Estimated Muon Flux Is Mainly Dependent On Z Asupporting
confidence: 86%
“…-The branching ratios, mass, lifetime of the charmed particles h and the critical energies of the charmed particle decay for pp K h 6 X inclusive reactions producing h charmed mesons through the decay D K K 1 m 1 n and L c K L 1 m 1 n[31].…”
mentioning
confidence: 99%
“…Even though neutrons which are produced in the cascade are not confined by the magnetic field, the amount of gas present is sufficient to prevent them from escaping. The hadronic cascade in the disk is much simpler than cascades in the earth's atmosphere [22,23,24], since the density of the accretion disk is so low that all unstable particles decay rather than interact. Therefore the cascade consists of a nucleonic part which feeds into the mesonic and electromagnetic channels; no pion-nucleon reactions occur.…”
Section: Hadronic Cascadesmentioning
confidence: 99%
“…The hadronic cascade in the disk is much simpler than cascades in the earth's atmosphere (Gaisser 1990, Gaisser & Yodh 1980, Gaisser et al 1978, since the density of the accretion disk is so low that all unstable particles decay rather than interact. Therefore the cascade consists of a nucleonic part which feeds into the mesonic and electro-magnetic channels; no pion-nucleon reactions occur.…”
Section: The Hadronic Cascade In the Accretion Diskmentioning
confidence: 99%